An analysis of wind band literature written for FLEX ensemble and full ensemble including Romanian Folk Dances composed by Bela Bartok arranged by Nakamura and Cosmopolitan America composed by Helen May Butler - Alexander, Shelly (Kansas State University, 2021)
The following report is research and analysis of major wind and percussion literature for the Graduate Conducting Recital performed by the Kansas State Wind Ensemble on (enter date here), under the direction of Shelly Alexander. This Graduate Conducting Recital will be performed by members of the Kansas State Wind Ensemble on (enter date here), under the direction of Shelly Alexander. The repertoire for the concerts will be comprised of the following two works: Romanian Folk Dances by Bela Bartok and Cosmopolitan America by Helen May Butler. This document contains thorough research and theoretical analysis to provide perspectives and strategies to adequately rehearse these pieces. This report contains documents consisting of rehearsal plans, Unit Studies, and Graph Analyses of the pieces.
Keywords: Wind band; Helen May Butler; Bela Bartok; Band; Music education; Conducting